THE PROFILE OF A PERFECT TEACHER: VULPE T. BUJOR-COSTICĂ (1924-1983) - PĂCURAR, AL. (Studia Universitatis Babeș-Bolyai Geographia, 2017)
Vulpe T. Bujor-Costică was for a short time a member of Institute of Geography belonging to Cluj University. In the second year as a student, he was asked by the head of the institute, professor Sabin Opreanu, to become a drawer at the Institute and he had this job between April and September 1947. Originating from an ancient Romanian family in Orăștie, Vulpe T. Bujor-Costică has been educated at the pre-communist Cluj Geographical School, whose bases were laid by the scientist George Vâlsan. He graduated in 1953 with a major in Geography, within the Faculty of Sciences of Cluj University. Between 1957 and 1983 he was a teacher at the Cluj School for Blind and Visually Impaired and an author of school books in Braille alphabet. At the same time, he activated in the “Iacob Mureșianu” male choir of the Cluj Culture Centre.